2019
DOI: 10.1088/1361-6641/ab2155
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of NO2 gas-sensing properties in InGaZnO thin-film transistors by a pre-biasing measurement method

Abstract: In this work, we investigated the effectiveness of a pre-biasing measurement technique for improving the gas-sensing performance of a metal oxide semiconductor (MOS)-based thin-film transistor (TFT)-type gas sensor for the first time. Various pre-biases voltages were applied to an indium-gallium-zinc oxide (IGZO) TFT gas sensor, and the resulting effects on NO 2 detection performances were examined at various NO 2 concentrations and temperatures. Our results showed that the NO 2 sensing performance of the IGZO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Transfer characteristics and output characteristics were measured by keeping V DS = 1 V and V GS = 15 V, respectively. It was observed that with the increase in NO 2 concentration, there was a positive shift in the V th and a decrease in the drain current ( I D ) of the TFT; this is consistent with the reported IGZO TFT-based sensors, , as shown in Figure a,b. There was a substantial change in the V th and I D of IGZO TFTs proportional to the concentration of NO 2 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Transfer characteristics and output characteristics were measured by keeping V DS = 1 V and V GS = 15 V, respectively. It was observed that with the increase in NO 2 concentration, there was a positive shift in the V th and a decrease in the drain current ( I D ) of the TFT; this is consistent with the reported IGZO TFT-based sensors, , as shown in Figure a,b. There was a substantial change in the V th and I D of IGZO TFTs proportional to the concentration of NO 2 .…”
Section: Resultssupporting
confidence: 90%
“…Because the channel of the TFT was oxidized after NO 2 exposure, these devices could not be recovered even after a prolonged N 2 purge (Figure a) owing to the strong bonding of gas molecules with the active area. Similarly, Kim et al observed the adsorption of NO 2 with an IGZO active layer and could not recover the device after exposure at room temperature. , The semiconducting channel properties could be revived only after the application of some external energy. Hence, we explored the revival of TFT sensors using light activation, as IGZO is reported to have excellent photoelectric characteristics .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxide semiconductors are used in various applications, including flat-panel displays [ 1 , 2 ], optical sensors [ 3 , 4 ], and solar cells [ 5 , 6 ], owing to their excellent electrical and optical properties. Among them, the amorphous-InGaZnO (a-IGZO) thin-film transistors (TFTs) have attracted considerable attention for applications in flat-panel displays thanks to their high electrical performances [ 7 , 8 , 9 , 10 , 11 , 12 ] and manufacturability over a large area [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, sensing performance improved when the temperature increases to 90°C possibly attributed to the effect of electric-field-induced chemisorptions of NO 2 at the channel of the IGZO TFTs. 65 Most of the TFT based sensor faces the problem of baseline recovery (return of base line resistance before gas exposure). Recovery rate of the TFT based sensor can be improved by irradiation UV light at the sensing channel.…”
mentioning
confidence: 99%